'Modern day Kolkata and mimicry of England': revisiting colonial nostalgia - Bandyopadhyay, Ranjan; Ray, Avishek (Social identities, 2025)
This paper explores the phenomenon of colonial nostalgia among middle-class and lower-middle-class residents in Kolkata and its surrounding suburbs - groups often overlooked in dominant discussions of postcolonial memory and urban identity. While nostalgia for the British Raj is typically associated with elites or nationalist critique, this study reveals how individuals with limited access to Anglophone cultural capital also express a complex longing for aspects of colonial rule. Drawing on ethnographic interviews, the paper shows how colonial memory endures through everyday practices, inherited social norms, and the built environment. Rather than interpreting this nostalgia as a simplistic yearning for the past, it is examined as a means through which contemporary frustrations, social aspirations, and contested identities are negotiated. The paper also reflects critically on the researchers' own positionality, emphasizing how class privilege and language fluency shaped field interactions and knowledge production. By centering non-elite perspectives and interrogating the epistemic frameworks through which nostalgia is interpreted, this study contributes to broader debates in postcolonial studies, memory studies, and urban anthropology. It calls for more reflexive, decolonized methodologies attuned to local complexities and everyday negotiations with the colonial past.